Longitudinal faster anxiety progression of GBA variant carriers in the early Parkinson’s disease cohort - Sang, Shushan; Ba, Yunpeng; Yang, Nannan (Frontiers in Neuroscience, 2024)
Objective Anxiety symptoms are prevalent neuropsychiatric manifestations in Parkinson’s disease (PD) and impact the development of motor complications. Our aim was to evaluate the association of GBA variants with the anxiety development in early PD cohort. Methods This cohort study used data from the Parkinson Progression Marker Initiative. The primary outcome anxiety was assessed by State–Trait Anxiety Inventory (STAI). The association between GBA and longitudinal change in the STAI total score was examined using linear mixed-effects model, and the association between GBA and anxiety progression was examined using Cox survival analysis. Results A total of 385 patients with PD were included in this study, 39 of them were GBA variant carriers and 346 were idiopathic PD without GBA variants. Patients with GBA variants had faster annual increase in anxiety score (β = 0.44; 95% CI, 0.18 to 0.71; p < 0.001) and were at higher risk of anxiety progression (HR 1.87; 95% CI, 1.03 to 3.41; p = 0.03,). Higher baseline scores for Scales for Outcomes in Parkinson’s Disease-Autonomic (SCOPA-AUT), which indicated the autonomic dysfunction, also independently predicted faster increase in anxiety score (β = 0.48; 95%CI, 0.19 to 0.69; p < 0.001) and higher incidence of anxiety development (HR = 1.05; 95% CI, 1.01 to 1.08; p = 0.008). Interpretation These findings suggest that longitudinal anxiety symptoms worsening was faster in PD patients who were GBA variant carriers and have dysautonomia, and this association was enhanced if they have both.